The East-West Culinary Conundrum: Cultural Authenticity in “The Hundred-Foot Journey” - Roy, Swagata Sinha; Subaramaniam, Kavitha (2017)
This paper attempts to examine the uniqueness of culinary identities as depicted in the 2014 film “The Hundred-foot Journey”, adapted from Richard Morais’ novel of the same name. The film details the passage of the Kadam family and their food heritage from Mumbai to London to the French Pyrenees where they encounter numerous hurdles before they are finally accepted by the locals in their restaurant enterprise. The thrust this study is to examine the challenges of survival and preservation of authentically Indian cuisine in a foreign Western environment. Further, food as a unifying force to bridge diverse nationalities will be deliberated. The competing restaurateur feels threatened at first but is later appreciative of other foreign delicacies. Identity, which is closely bound with culture, familial associations and at times geographical terrain, could diffuse into newer traditions and values. The textual analysis approach is found to be the most appropriate to explore the film genre whereby the researchers will explain the relevance of food culture in the context of identity.